Strategic management of Qafco - Mandani, Abdulhameed E. (Animo Repository, 1998)
Qatar Fertilizer Company is a joint venture that produces mineral fertilizer. The establishment makes a significant step to industrial diversification program of Qatar by using of the natural gas resources. The said company is owned by Qatar General Petroleum Corporation (75%) and Norsk Hydro of Norway (25%). Qafco is producing ammonia and urea using feed gas from the other subsidiary of QGPC. The company markets its products in various markets, mostly in Asia. Norsk Hydro has contract with Qafco to provide technical advisory and market parts of Qafcos production for a free. Although there are many players in Asia, the demand for fertilizer has often been greater than the supply. The price of the products is dictated by the supply and demand of the environment. Monetary crisis also plays an important role in determining fertilizer production and prices. The price is usually in U.S. dollar and because of the currency crisis in Asia, the price was negatively affected. Despite of this Qafco has not incurred losses. The profitability for 1995 and 1996 was 33% and 24% respectively. Qafcobuilt a new plant (Qafco 3) and started production in 1997. Qafco 1 and Qafco 2 plants have been producing over design capacity due to improvement. The technologies vary in the three plants. The technologies in fertilizer production contribute significantly to the efficiency of the plants. Having identified the fertilizer industry and made the analysis, the researcher proposes that the company invests in expanding and continuously improving the production facilities in order to tap the opportunities and therefore prosper. In addition, the company should invest on information technology, strengthen its ties with the government and increase the number of contractual customers. The researchers also made a projection of the balance Sheet and the Income Statement until year 29006, when the company may not longer enjoy tax holidays.